The directory of athletic scholarships - Green, Barry; Green, Alan (Putnam, 1981)
A complete, up-to-date listing of colleges and universities that offer scholarships to athletes, and of the sports for which scholarships are offered.
Keywords: Sports - États-Unis - Bourses d'études - Répertoires; Universités - États-Unis - Répertoires; Sports -- Scholarships, fellowships, etc. -- Directories; Sports -- Scholarships, fellowships, etc. -- United States -- Directories; Universities and colleges -- Directories; Universities and colleges -- United States -- Directories; Sport; Ausbildungsstätte; USA; Adressbuch